KEMAMPUAN PELAFALAN KOSAKATA BUNYI PANJANG (CHOUON) MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Nur Rofiah Utari Br. Aritonang; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to examine the ability of students to pronounce Japanese vocabulary containing long sounds (chouon). This study uses a quantitative descriptive method with the research instrument in the form of a pronunciation test. The sample in this study was the class of 2020 students of the Riau University Japanese language education study program, with a total of 10 people using the random choice technique. The data in this study were recordings of long sounds (chouon) and analysed using the Praat application. It was found that the students' pronunciation of long-sounding vocabulary (chouon) tended to be good at the beginning and less so at the end.Key Words: Pronuncation, Long Vowel, Student